The impact of incline and speed of treadmill on ankle muscle activity in middle-aged adults. Issue 2 (April 2017) - Mohammadi, Roghayeh; Phadke, Chetan P.
Summary: Objective: Additional demands associated with changing walking incline and speed combined with normal aging related changes in muscle recruitment can make walking difficult. This study examined the effects of walking on a treadmill at different inclines and speeds on ankle muscles in healthy middle-aged adults. Methods: Fifteen healthy subjects (10M/5F) walked on a standard treadmill at three different inclines (0°, 3°, and 6°) and speeds (self-selected, self-selected+20%, self-selected+40%). The electromyographic activity of Medial Gastrocnemius (MG), and Tibialis anterior (TA) muscles was measured during the push off phase of the gait. Results: Bilateral MG muscle activity increased when subjects walked uphill compared with level walking (p < 0.05), but no changes were seen with increasing walking speed (p > 0.05). Right MG (dominant side) activity increased at all inclines, but only at 6° on left side and also MG muscle activity was delayed on the left side at faster speed (p < 0.05). Conclusion: The bias towards using muscles in the dominant leg in middle-aged subjects to overcome challenging walking conditions may be an age-related adaptation. These results suggest that future studies in the stroke population are needed to examine the impact of hemiparesis of the dominant leg as this group of persons post-stroke may be more likely to experience greater impairment of muscle activation patterns during walking on sloped surfaces.